Evaluation of physicians’ knowledge of deprescribing, deprescribing tools and assessment of factors afecting deprescribing process (2023)
Background Polypharmacy is a common global health concern in the older population. Deprescribing has been acknowledged as an important aspect of medication use review that helps to reduce polypharmacy, inappropriate medication uses and medication adverse events, thus ensuring medication optimization and improving healthrelated quality of life. As physicians are primarily responsible for prescribing and monitoring of drug therapy, their perception of deprescribing and knowledge of available deprescribing tools is highly important. This study aimed to explore physicians’ knowledge of deprescribing, deprescribing tools and factors that may afect the deprescribing process. Methods This was a cross-sectional survey carried out among 70 physicians in selected units of a teaching hospital in Nigeria between May and June 2022. Social-demographic information, knowledge of deprescribing and depre scribing tools were obtained using a self-administered, semi-structured questionnaire, while barriers and enablers of medication deprescribing were assessed with modifed Revised Patients’ Attitudes Towards Deprescribing (rPATD) Questionnaire. Descriptive and bivariate analyses were carried out using SPSS and α was set at p= 0.012), while knowledge of deprescribing tools was signif cantly associated with; awareness of the term “deprescribing” (p= 0.029), and daily encounters with older multimorbid patients (p=0.031). Very important factor afecting physicians deprescribing decisions include beneft of the medica tion. The most common barrier is lack of information for a full clinical picture of the patient. Conclusion The physicians had good knowledge of the term “deprescribing” and the steps to deprescribing. Specifc measures to target the barriers faced by the physicians in deprescribing medications and policies to implement physi cians use of existing guidelines to facilitate their deprescribing decisions are essential.